High-temperature-resistant and oil-resistant cable and preparation method and application thereof
Patent Information
- Application Number
- CN202611429199.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-27
AI Technical Summary
1.本发明通过内外层交联剂差异化配比形成梯度交联结构,内层保证高温尺寸稳定性与介电性能,外层兼具柔韧性、耐油性与阻燃性,双层硫化后界面化学键合紧密,无分层缺陷。
Smart Images

Figure CN122991737A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of special cable technology, and in particular to a high-temperature resistant and oil-resistant cable, its preparation method and application. Background Technology
[0002] The temperature inside an oil well can reach 150℃~200℃, and the medium contains corrosive components such as crude oil, brine, and hydrogen sulfide, which have significant swelling, degradation, and penetrating erosion effects on polymer materials. Under these conditions, the cable is in a high-temperature and highly corrosive environment for a long time. At the same time, during the pulling and lowering operations and the reciprocating operation of the pumping unit, the cable needs to withstand repeated tensile, compressive, and bending loads, which can easily lead to insulation layer cracking, interface delamination, and mechanical fatigue.
[0003] Existing submersible pump cable insulation systems mostly use a single material, such as EPDM rubber or polypropylene. Although these materials have certain temperature resistance, they are prone to thermal-oxidative aging, cross-linking structure deterioration, and oil swelling under long-term high temperatures and the combined effects of oil and gas media. This leads to a decrease in insulation strength and a decline in mechanical properties, making it difficult to meet the long-term service requirements of deep well operations. Some products use a polyimide-F46 composite film wrapping structure, which has a higher temperature resistance rating, but the process is complex and costly. Furthermore, air gaps are easily formed between the film layers, which can easily induce partial discharge under alternating electric fields, ultimately causing insulation breakdown.
[0004] While existing technologies have proposed improved solutions for filling the gaps in armor with polymers, they only focus on the external protective structure and do not address the long-term stability issues under multi-field coupling conditions from the perspective of insulation material system and structural design. They cannot simultaneously take into account temperature resistance, oil resistance, insulation, and mechanical properties. Summary of the Invention
[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a high-temperature and oil-resistant cable with good long-term stability.
[0006] The details are as follows: The first aspect of this application provides a high-temperature and oil-resistant cable, comprising a conductor, an inner insulation layer, an outer insulation layer, a water-blocking layer, a composite sheath layer, and an interlocking armor layer; The amount of crosslinking agent used in the inner insulation layer is higher than that in the outer insulation layer; The raw materials for preparing the composite sheath layer include chlorosulfonated polyethylene rubber and polytetrafluoroethylene micro powder; The raw materials for preparing the inner insulating layer include modified boron nitride; The method for preparing the modified boron nitride includes the following steps: Boron nitride is reacted with a vinyl ionic liquid, acrylate, and an initiator.
[0007] The high-temperature and oil-resistant cable according to the present invention has at least the following beneficial effects: 1. This invention forms a gradient crosslinking structure by using a differential ratio of crosslinking agents in the inner and outer layers. The inner layer ensures high-temperature dimensional stability and dielectric properties, while the outer layer combines flexibility, oil resistance, and flame retardancy. After double-layer vulcanization, the interface chemical bonds are tight and there are no delamination defects.
[0008] 2. Adding modified boron nitride to the internal insulation can improve thermal conductivity and heat dissipation, and also hinder oxygen penetration, thus significantly extending the thermal and oxidative aging life.
[0009] 3. The composite sheath layer adopts a blend system of chlorosulfonated polyethylene and polytetrafluoroethylene micro powder, which effectively improves scratch resistance and oil swelling resistance.
[0010] According to some embodiments of the present invention, the crosslinking agent content of the inner insulation layer being higher than that of the outer insulation layer means that, under the condition of the same base material content, the crosslinking agent content is higher.
[0011] According to some embodiments of the present invention, the method for preparing the modified boron nitride includes the following steps: S1. Boron nitride is dispersed in a solvent to obtain a first mixture; S2. Add vinyl ionic liquid, acrylate and initiator to the first mixture and react.
[0012] According to some embodiments of the present invention, the solvent is at least one of anhydrous ethanol or N,N-dimethylformamide.
[0013] According to some embodiments of the present invention, the dispersion time is 30 min to 60 min.
[0014] According to some embodiments of the present invention, the vinyl ionic liquid is 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide.
[0015] According to some embodiments of the present invention, the acrylate is at least one of ethylene glycol dimethacrylate and ethoxylated trimethylolpropane triacrylate.
[0016] According to some embodiments of the present invention, the acrylate is ethylene glycol dimethacrylate.
[0017] According to some embodiments of the present invention, the initiator is at least one selected from azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylpentanonitrile), and dimethyl azobisisobutyrate.
[0018] According to some embodiments of the present invention, the initiator is azobisisobutyronitrile.
[0019] According to some embodiments of the present invention, the mass ratio of boron nitride to vinyl ionic liquid is 1:0.2-0.5.
[0020] According to some embodiments of the present invention, the mass ratio of boron nitride to acrylate is 1:0.04~0.05.
[0021] According to some embodiments of the present invention, the mass ratio of boron nitride to initiator is 1:0.015~0.025.
[0022] According to some embodiments of the present invention, the reaction atmosphere in step S2 is nitrogen.
[0023] According to some embodiments of the present invention, the reaction time in step S2 is 6h to 12h.
[0024] According to some embodiments of the present invention, the reaction temperature in step S2 is 70°C to 80°C.
[0025] Ionic liquid monomers undergo in-situ polymerization on the surface of boron nitride, forming a polyionic liquid coating layer. This process significantly improves the surface polarity and interfacial compatibility of boron nitride, resulting in more uniform dispersion and less agglomeration within the EPDM rubber matrix. This fully leverages the high thermal conductivity and lamellar barrier properties of boron nitride, while also enhancing the interfacial bonding between the filler and the rubber matrix and reducing interfacial defects. The resulting more continuous thermal pathways further improve the thermal conductivity and heat dissipation efficiency of the insulation layer. Simultaneously, it strengthens the shielding effect against oxygen and heat media, significantly inhibiting thermo-oxidative aging. This allows the cable to maintain stable mechanical and electrical insulation properties under long-term high-temperature conditions, extending its service life.
[0026] According to some embodiments of the present invention, the inner insulating layer comprises the following raw materials in parts by weight: 100 parts base material, 3.5 to 4.5 parts crosslinking agent, 1.2 to 1.8 parts co-crosslinking agent, and 8 to 12 parts modified boron nitride.
[0027] According to some embodiments of the present invention, the base material in the inner insulation layer is ethylene propylene diene monomer (EPDM) rubber.
[0028] According to some embodiments of the present invention, the crosslinking agent in the inner insulation layer is dicumyl peroxide. According to some embodiments of the present invention, the co-crosslinking agent in the inner insulation layer is triallyl isocyanurate.
[0029] According to some embodiments of the present invention, the D50 of the modified boron nitride in the inner insulating layer is 45nm~55nm.
[0030] Adding modified boron nitride to the inner insulation layer not only improves the thermal conductivity, but its layered structure also hinders oxygen penetration at high temperatures, significantly improving the thermal oxidative aging life.
[0031] If the amount of crosslinking agent in the inner insulation layer is less than 3.5 parts, the gradient effect weakens, the difference in crosslinking degree between the inner and outer layers is too small, and an effective mechanical buffer interface cannot be formed. As a result, after high-temperature aging, the molecular chains of the inner layer are prone to slippage, and the tensile strength retention rate drops sharply. If the amount of crosslinking agent is more than 4.5 parts, the crosslinking of the inner layer is too high, the material becomes brittle, and cracking is likely to occur when bending at low temperatures.
[0032] According to some embodiments of the present invention, the outer insulation layer comprises the following raw materials in parts by weight: 100 parts base material, 25 to 42 parts modifier, 2.5 to 3.0 parts crosslinking agent, 1.25 to 2.8 parts antioxidant, and 50 to 70 parts flame retardant.
[0033] According to some embodiments of the present invention, the base material in the outer insulation layer is an ethylene-vinyl acetate copolymer.
[0034] According to some embodiments of the present invention, the vinyl acetate content in the ethylene-vinyl acetate copolymer is 35% to 45%.
[0035] According to some embodiments of the present invention, the modifier in the outer insulation layer is linear low-density polyethylene.
[0036] Linear low-density polyethylene has good processing fluidity, low-temperature toughness, mechanical strength and electrical insulation properties. It can improve the extrusion moldability, mechanical strength and dimensional stability of ethylene-vinyl acetate copolymer matrix, enhance the temperature resistance, environmental stress cracking resistance and electrical insulation properties of insulation layer, and has good compatibility with other components in the system, ensuring the stability of the bilayer co-extrusion molding and vulcanization interface.
[0037] According to some embodiments of the present invention, the crosslinking agent in the outer insulating layer is dicumyl peroxide.
[0038] According to some embodiments of the present invention, the antioxidant in the outer insulating layer is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].
[0039] According to some embodiments of the present invention, the flame retardant in the outer insulation layer is magnesium hydroxide.
[0040] According to some embodiments of the present invention, the composite sheath layer comprises the following raw materials in parts by weight: 100 parts base material, 25 to 35 parts reinforcing agent, 12 to 18 parts plasticizer, 5 to 10 parts oil-resistant modifier, and 1.5 to 2.5 parts vulcanizing agent.
[0041] According to some embodiments of the present invention, the base material in the composite sheath layer is chlorosulfonated polyethylene rubber.
[0042] According to some embodiments of the present invention, the reinforcing agent in the composite sheath layer is fumed silica.
[0043] According to some embodiments of the present invention, the plasticizer in the composite sheath layer is trioctyl trimellitate.
[0044] According to some embodiments of the present invention, the oil-resistant modifier in the composite sheath layer is polytetrafluoroethylene micro powder.
[0045] According to some embodiments of the present invention, the vulcanizing agent in the composite sheath layer is N,N-m-phenylenebismaleimide.
[0046] According to some embodiments of the present invention, the D50 of the polytetrafluoroethylene micropowder in the composite sheath layer is 3μm~7μm.
[0047] Adding PTFE micropowder to chlorosulfonated polyethylene sheaths significantly reduces the surface friction coefficient of the sheath by utilizing its extremely low surface energy and excellent lubricity. Furthermore, the PTFE micropowder forms a self-lubricating dispersed phase in the rubber matrix, which significantly improves the sheath's scratch resistance and oil swelling resistance.
[0048] If the amount of oil-resistant modifier in the casing is less than 5 parts, the oil volume expansion rate exceeds 35%, and the surface friction coefficient of the casing is high, making it prone to damage during downhole friction with the casing. If the amount is more than 10 parts, the compatibility between the oil-resistant modifier and the base material deteriorates, resulting in a rough surface during extrusion and a significant decrease in tensile strength.
[0049] A method for preparing the above-mentioned high-temperature resistant and oil-resistant cable according to a second aspect of the present invention includes the following steps: An inner insulation layer, an outer insulation layer, a water-blocking layer, a composite sheath layer, and an interlocking armor layer are sequentially formed on the outside of the treated conductor.
[0050] According to some embodiments of the present invention, the method for preparing the high-temperature and oil-resistant cable includes the following steps: Step 1, Conductor treatment: Select tightly stranded tin-plated annealed copper conductors, and coat the surface with an epoxy-type tackifier to form an adhesive layer; Step 2, Double-layer co-extrusion coating: The inner and outer insulation layers are coated onto the conductor surface using a simultaneous extrusion process; Step 3, Continuous vulcanization: The extruded wire core is subjected to continuous vulcanization treatment with saturated water vapor to obtain a single insulated wire core; Step 4, Cable Formation and Water-Blocking Layer Wrapping: Twist several insulated wire cores into a cable core and wrap it with a semi-conductive water-resistant expansion strip. Step 5, Sheath Extrusion and Vulcanization: The composite sheath material is extruded and coated on the outside of the water-blocking layer, and then vulcanized in a salt bath.
[0051] Step Six: Interlocking Armor: Galvanized steel strips are wrapped around the outer sheath, using an interlocking armor structure.
[0052] According to some embodiments of the present invention, in step two, the extrusion temperature of the inner insulating layer is 90°C to 110°C.
[0053] According to some embodiments of the present invention, in step two, the extrusion temperature of the outer insulating layer is 105°C to 125°C.
[0054] The inner insulation layer, with its high dicumyl peroxide content, forms a high-crosslink density network after vulcanization, ensuring elasticity and electrical stability at high temperatures. The outer insulation layer, with its lower dicumyl peroxide content, forms a medium-crosslink density network. The outer insulation layer is rich in polar ethylene-vinyl acetate copolymer and magnesium hydroxide, providing excellent oil resistance and flame retardancy.
[0055] According to some embodiments of the present invention, in step three, the pressure of saturated steam treatment is 2.0 MPa to 2.5 MPa.
[0056] According to some embodiments of the present invention, in step three, the temperature of the saturated steam treatment is 195°C to 205°C.
[0057] According to some embodiments of the present invention, in step three, the linear velocity of the vulcanization process is 15 m / min to 25 m / min.
[0058] By adjusting the linear velocity within the range of 15m / min to 25m / min, a gradient match is formed between the inner and outer layers in terms of cross-linking kinetics, achieving defect-free interface fusion.
[0059] According to some embodiments of the present invention, in step five, the temperature of salt bath sulfidation is 230°C to 240°C.
[0060] According to some embodiments of the present invention, in step six, a gap of 0.75mm ± 0.25mm is reserved between the inner diameter of the armor and the outer diameter of the sheath.
[0061] A floating armor structure is formed by leaving a gap of 0.75mm±0.25mm between the inner diameter of the armor and the outer diameter of the sheath to provide radial compression resistance and bending flexibility.
[0062] According to a third aspect of this application, an application of the above-mentioned high-temperature and oil-resistant cable is included, specifically the application of the high-temperature and oil-resistant cable described in any one of the above-mentioned methods or the high-temperature and oil-resistant cable obtained by the above-mentioned preparation method in the fields of downhole oil well extraction, submersible pump power supply, wellbore power transmission, and high-temperature and high-pressure oil and gas well working conditions. Attached Figure Description
[0063] To more clearly illustrate the technical solutions in the embodiments of this drawing or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this drawing. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0064] Figure 1 This is a schematic diagram of the cable cross-section structure of the present invention.
[0065] Explanation of icon numbers: 1. Conductor; 2. Adhesive layer; 3. Inner insulation layer; 4. Outer insulation layer; 5. Water-blocking layer; 6. Composite sheath layer; 7. Interlocking armor layer.
[0066] The purpose, features, and advantages of this accompanying drawing will be further explained in conjunction with the embodiments and with reference to the accompanying drawing. Detailed Implementation
[0067] To make the objectives, technical solutions, and advantages of this application clearer, the following description and illustration are provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application. All other embodiments obtained by those skilled in the art based on the embodiments provided in this application without inventive effort are within the scope of protection of this application.
[0068] Obviously, the following description is merely some examples or embodiments of this application. Those skilled in the art can apply this application to other similar scenarios without any inventive effort. Furthermore, it is understood that although the effort involved in such development may be complex and lengthy, for those skilled in the art related to the content disclosed in this application, any changes to design, manufacturing, or production based on the technical content disclosed in this application are merely conventional technical means and should not be construed as insufficient disclosure of the content of this application.
[0069] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0070] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0071] The following are some of the raw materials used in the embodiments of this application: The EPDM rubber used is 4725P; The D50 of boron nitride is 50 nm; The ethylene-vinyl acetate copolymer used is Elvax 40L-03, with a vinyl acetate content of 40%. The linear low-density polyethylene used is DNDA-7144; The pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] ester used is Irganox 1010; The magnesium hydroxide used is HX-6000, D. 50 ≤1.8μm, D 97 ≤3.2μm, specific surface area ≥19 m² 2 / g; The chlorosulfonated polyethylene rubber used is Hypalon 40, with a chlorine content of 35% and a Mooney viscosity of 41–60 (ML 1+4, 100℃). The fumed silica used is AEROSIL R974; The trioctyl trimellitate used is TOTM-98; The N,N-m-phenylenebismaleimide used is HVA-2; The polytetrafluoroethylene micro powder used is Zonyl MP 1100, with a D50 of 5μm; The epoxy tackifier used is A-187; The manufacturer of the semiconducting resistive water expansion tape is Yangzhou Tengfei Cable & Electrical Materials Co., Ltd.
[0072] Example 1 A high-temperature and oil-resistant cable includes a conductor 1, an adhesive layer 2, an inner insulation layer 3, an outer insulation layer 4, a water-blocking layer 5, a composite sheath layer 6, and an interlocking armor layer 7.
[0073] The inner insulation layer comprises the following raw materials: 100 parts of EPDM rubber, 4.2 parts of dicumyl peroxide, 1.5 parts of triallyl isocyanurate, and 10 parts of modified boron nitride.
[0074] The outer insulation layer comprises the following raw materials: 100 parts of ethylene-vinyl acetate copolymer, 30 parts of linear low-density polyethylene, 2.5 parts of dicumyl peroxide, 1.6 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 60 parts of magnesium hydroxide.
[0075] The composite sheath layer comprises the following raw materials: 100 parts of chlorosulfonated polyethylene rubber, 30 parts of fumed silica, 15 parts of trioctyl trimellitate, 8 parts of polytetrafluoroethylene micro powder, and 2 parts of N,N-m-phenylenebismaleimide.
[0076] The preparation method of modified boron nitride is as follows: Boron nitride powder was dispersed in anhydrous ethanol and ultrasonically treated for 60 min. Vinyl ionic liquid monomers (1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide), ethylene glycol dimethacrylate and azobisisobutyronitrile were added to the dispersion.
[0077] Under nitrogen protection, the temperature was raised to 80°C and the reaction was stirred for 12 hours.
[0078] The mass ratio of boron nitride to vinyl ionic liquid is 1:0.2; The mass ratio of boron nitride to ethylene glycol dimethacrylate is 1:0.05; The mass ratio of boron nitride to initiator is 1:0.02.
[0079] The manufacturing process of this high-temperature and oil-resistant cable is as follows: S1, Conductor treatment: The conductor is a tightly stranded tin-plated annealed copper conductor with a soft stranded structure of electrical oxygen-free copper (Cu-ETP). The average thickness of the tin plating layer on the conductor surface is 0.8 μm, with a minimum local thickness of 0.5 μm. The conductor undergoes a compaction treatment with a compaction coefficient of 90%. An epoxy-based tackifier is uniformly coated on the conductor surface to form an adhesive layer with a thickness of 0.05 mm. S2, double-layer co-extrusion and gradient cross-linking: The inner and outer insulation materials are simultaneously extruded and coated onto the outside of the conductor: The extrusion temperature of the inner insulation layer is 100℃; The extrusion temperature of the outer insulation layer is 120℃; S3, Continuous vulcanization: The extruded wire core is subjected to continuous saturated steam vulcanization. The steam pressure is 2.0 MPa and the temperature is 200℃. The linear velocity during the vulcanization process is 20 m / min, resulting in a single insulated wire core.
[0080] S4. Cable forming and water-blocking layer wrapping: Three insulated wire cores are twisted together to form a cable core, and a 0.3mm thick semi-conductive water-expanding tape (polyester non-woven fabric base, containing conductive carbon black and super absorbent resin) is wrapped around the cable core with a wrapping overlap rate of 30%. S5, Sheath Extrusion: A composite sheath layer is extruded and coated on the outside of the water-blocking layer, and vulcanization and shaping are completed using a 240℃ molten nitrate mixed salt bath (potassium nitrate 53% + sodium nitrite 40% + sodium nitrate 7%). S6, Interlocking Armor: A galvanized steel strip is wrapped around the outer sheath to form an interlocking armor structure. A gap of 0.75mm ± 0.25mm is reserved between the inner diameter of the armor and the outer diameter of the sheath to form a floating armor structure.
[0081] Example 2 A high-temperature and oil-resistant cable is basically the same as that in Example 1, except that: (1) In the inner insulation layer, the amount of dicumyl peroxide is changed to 4.0 parts; (2) In the inner insulation layer, the number of modified boron nitride is changed to 8 parts.
[0082] The preparation method of this high-temperature and oil-resistant cable is as described in Example 1.
[0083] Example 3 A high-temperature and oil-resistant cable is basically the same as that in Example 1, except that: (1) In the outer insulation layer, the amount of dicumyl peroxide is changed to 2.8 parts; (2) In the outer insulation layer, the amount of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] is changed to 2.0 parts.
[0084] The preparation method of this high-temperature and oil-resistant cable is as described in Example 1.
[0085] Example 4 A high-temperature and oil-resistant cable is basically the same as that in Example 1, except that: In the inner insulation layer, the amount of modified boron nitride is changed to 12 parts.
[0086] The preparation method of this high-temperature and oil-resistant cable is as described in Example 1.
[0087] Comparative Example 1 A cable, essentially the same as in Example 1, differs in that: No modified boron nitride is added to the inner insulation layer.
[0088] The cable was prepared according to Example 1.
[0089] Comparative Example 2 A cable, essentially the same as in Example 1, differs in that: The content of dicumyl peroxide in both the inner and outer insulation layers is 3.5 parts.
[0090] The cable was prepared according to Example 1.
[0091] Performance testing: 1. Thermal aging performance test: Aging temperature: 158℃, aging time: 168h. The tensile strength and elongation at break of the samples before and after aging were tested, and the retention rate was calculated.
[0092] 2. Oil resistance test: IRM903 oil was used to immerse the sample at 121℃ for 7 days. The tensile strength and elongation at break of the sample before and after oil immersion were tested, and the performance retention rate was calculated.
[0093] 3. Low temperature bending test: Place the cable sample in a low temperature chamber at -40℃±2℃ for ≥16 hours to ensure temperature equilibrium. After taking it out, wind it around a test rod with a diameter of 5 times the outer diameter of the sample within 1 minute and check whether there are visible cracks in the insulation or sheath.
[0094] Each group of the examples and each group of the comparative examples were tested according to the above test standards, and the test results are shown in Table 1.
[0095]
[0096] As shown in Table 1, the thermal aging, oil resistance, and low-temperature bending performance of Examples 1-4 of this application are significantly better than those of Comparative Example 1 and Comparative Example 2. The higher retention rates of strength and elongation after thermal aging in the Examples are attributed to the antioxidant and thermal conductivity effects of modified boron nitride, combined with the gradient cross-linking structure of the inner and outer layers, which makes the insulation layer more stable at high temperatures. In the oil resistance test, the Examples showed high tensile strength retention and low volume expansion rate after oil immersion, mainly due to the synergistic oil resistance effect of the high-polarity EVA outer insulation and the polytetrafluoroethylene micropowder sheath. In the low-temperature bending test, none of the Examples showed cracking, indicating that the gradient cross-linking structure resulted in better stress matching and toughness between the inner and outer layers.
[0097] Comparative Example 1, without the addition of modified boron nitride, lacks the functional components for thermal conductivity and oxygen blocking. Therefore, its mechanical properties are significantly reduced after thermal aging, and its thermal conductivity and shielding ability decrease. It is more prone to swelling and damage in oil media. After oil immersion, its performance retention rate is low, and its volume expansion rate is as high as 45%. Furthermore, microcracks appear when bending at low temperature. This fully demonstrates that modified boron nitride is a key component for improving the thermal aging, oil resistance, and low-temperature toughness of cables.
[0098] In Comparative Example 2, the amount of crosslinking agent used in the inner and outer insulation layers was the same, and no gradient crosslinking structure was formed. Since modified boron nitride was still added in this group, relying on the excellent thermal conductivity and oxygen barrier properties of boron nitride, its thermal aging performance was not much different from that of the example; however, the crosslinking density of the inner and outer insulation layers was the same, and the properties of the two layers did not form a differentiated adaptation, resulting in a significant decrease in the insulation structure's ability to resist oil penetration, a significant decrease in the ability to inhibit swelling, a decrease in the retention rate of mechanical properties after oil immersion, and a significant increase in the volume expansion rate.
[0099] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A high-temperature and oil-resistant cable, characterized in that, It includes a conductor, an inner insulation layer, an outer insulation layer, a water-blocking layer, a composite sheath layer, and an interlocking armor layer; The amount of crosslinking agent used in the inner insulation layer is higher than that in the outer insulation layer; The raw materials for preparing the composite sheath layer include chlorosulfonated polyethylene rubber and polytetrafluoroethylene micro powder; The raw materials for preparing the inner insulating layer include modified boron nitride; The method for preparing the modified boron nitride includes the following steps: Boron nitride is reacted with a vinyl ionic liquid, acrylate, and an initiator.
2. The high-temperature and oil-resistant cable as described in claim 1, characterized in that, The inner insulation layer comprises the following raw materials in parts by weight: 100 parts base material, 3.5 to 4.5 parts crosslinking agent, 1.2 to 1.8 parts co-crosslinking agent, and 8 to 12 parts modified boron nitride.
3. The high-temperature and oil-resistant cable as described in claim 1, characterized in that, It satisfies at least one of the following characteristics (1) to (2): (1) The D50 of the modified boron nitride in the inner insulating layer is 45nm~55nm; (2) The D50 of the polytetrafluoroethylene micro powder is 3μm~7μm.
4. The high-temperature and oil-resistant cable as described in claim 2, characterized in that, The inner insulating layer satisfies at least one of the following characteristics (1) to (3): (1) The base material is ethylene propylene diene monomer (EPDM) rubber; (2) The crosslinking agent is dicumyl peroxide; (3) The crosslinking agent is triallyl isocyanurate.
5. The high-temperature and oil-resistant cable as described in claim 1, characterized in that, The outer insulation layer comprises the following raw materials in parts by weight: 100 parts base material, 25 to 42 parts modifier, 2.5 to 3.0 parts crosslinking agent, 1.25 to 2.8 parts antioxidant, and 50 to 70 parts flame retardant.
6. The high-temperature and oil-resistant cable as described in claim 5, characterized in that, The outer insulating layer satisfies at least one of the following characteristics (1) to (5): (1) The base material is an ethylene-vinyl acetate copolymer; (2) The modifier is linear low-density polyethylene; (3) The crosslinking agent is dicumyl peroxide; (4) The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; (5) The flame retardant is magnesium hydroxide.
7. The high-temperature and oil-resistant cable as described in claim 1, characterized in that, The composite sheath layer comprises the following raw materials in parts by weight: 100 parts of chlorosulfonated polyethylene rubber, 25 to 35 parts of reinforcing agent, 12 to 18 parts of plasticizer, 5 to 10 parts of polytetrafluoroethylene micro powder, and 1.5 to 2.5 parts of vulcanizing agent.
8. The high-temperature and oil-resistant cable as described in claim 7, characterized in that, The composite sheath layer satisfies at least one of the following characteristics (1) to (3): (1) The reinforcing agent is fumed silica; (2) The plasticizer is trioctyl trimellitate; (3) The vulcanizing agent is N,N-m-phenylenebismaleimide.
9. A method for preparing a high-temperature resistant and oil-resistant cable as described in any one of claims 1 to 8, characterized in that, An inner insulation layer, an outer insulation layer, a water-blocking layer, a composite sheath layer, and an interlocking armor layer are sequentially formed on the outside of the treated conductor.
10. A high-temperature resistant and oil-resistant cable as described in any one of claims 1 to 8, or a high-temperature resistant and oil-resistant cable prepared by the preparation method as described in claim 9, characterized in that, The high-temperature and oil-resistant cables are used in oil well drilling, submersible pump power supply, wellbore power transmission, and high-temperature and high-pressure oil and gas well operations.